THE CONTRIBUTION OF THE DEFENCE ACT TO THE FIGHT AGAINST PIRACY - PHG Vrancken; SV Hoctor (Obiter, 2021)
The recent events off the Horn of Africa have drawn attention again to the problem of piracy. Less publicized is an increase in pirate activities in West Africa. Despite centuries of repression, this criminal behaviour continues to present a serious challenge to the safety of shipping on which international trade depends. And the phenomenon is spreading worryingly close to a South African coast which witnessed it in the past. Indeed, pirates operated off the coast of Southern Africa as early as 1508, with pirate activity peaking at the end of the 17th century. Piracy may be generally defined as “unlawful depredation at sea involving the use or threat of violence possibly, but not necessarily, involving robbery”. The purpose of this paper is to examine the contribution of the Defence Act 42 of 2002 (hereinafter “the Act”) to the fight against piracy. South Africa has a duty to co-operate to the fullest possible extent in the repression of piracy on the high seas in terms of the 1982 UN Convention on the Law of the Sea (hereinafter “LOSC”) (art 100. South Africa ratified LOSC in 1997 after it had come into effect in 1994). In order to do so, South Africa is expected to exercise its legislative, executive and judicial jurisdictions.